DOI: 10.14264/uql.2015.535
|View full text |Cite
|
Sign up to set email alerts
|

The biochemical and microbiological characteristics of rumen fluid from cattle co-grazed with and without camels as compared to that from the foregut of camels

Abstract: Co-grazing is a common practice under many range conditions. The main advantage of co-grazing is to fully utilize the vegetation sources by taking advantage of the different preferences among animals towards plant species and parts. Hence, this study aimed to establish if co-grazing camels with cattle would lead to changes in the biochemical characteristics in the rumen contents of cattle, and result in different fermentation end products. Rumen contents were collected from two groups of animals at two differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 166 publications
(219 reference statements)
0
4
0
Order By: Relevance
“…The culturing of bacteria was carried out using culture-dependent techniques in roll tubes, while identification was carried out using molecular techniques based on the 16S rRNA gene ( Ghali et al, 2004 , 2011 ). Moving on with the technology, further studies applied culture-independent molecular techniques, first by constructing clone libraries and later by using new generation sequencing technologies and genome analysis ( Samsudin et al, 2011 , 2012 , 2014 ; Suyub, 2014 , Seshadri et al, 2018 ; Rabee et al, 2020 ).…”
Section: The Microbial Ecology Of the Forestomach Of The Arabian Camelmentioning
confidence: 99%
See 3 more Smart Citations
“…The culturing of bacteria was carried out using culture-dependent techniques in roll tubes, while identification was carried out using molecular techniques based on the 16S rRNA gene ( Ghali et al, 2004 , 2011 ). Moving on with the technology, further studies applied culture-independent molecular techniques, first by constructing clone libraries and later by using new generation sequencing technologies and genome analysis ( Samsudin et al, 2011 , 2012 , 2014 ; Suyub, 2014 , Seshadri et al, 2018 ; Rabee et al, 2020 ).…”
Section: The Microbial Ecology Of the Forestomach Of The Arabian Camelmentioning
confidence: 99%
“…Earlier studies in our laboratory using high-throughput pyrosequencing of 16S rRNA provided us with detailed information on the microbiome diversity and complexity of Australian feral camels ( Camelus dromedarius ). Results of the taxonomic analyses yielded 21 bacterial phylotypes with Bacteroidetes and Firmicutes being the most abundant with 56.5% and 19.3%, respectively ( Suyub, 2014 ). Similarly, Bhatt et al (2013) reported a relative abundance rate of 55.5 for Bacteroidetes in handfed camels.…”
Section: Fiber-degrading Bacteriamentioning
confidence: 99%
See 2 more Smart Citations